PERSPECTIVES ON CANON HISTORY AND CANONICAL CRITICISM IN THE LIGHT OF BIBLICAL SPIRITUALITY - De Villiers, Pieter G. R. (Scriptura, 2006)
This essay discusses various aspects of a recent publication in the light of the study of canon history and canonical criticism. It first provides an overview of the reasons for the renewed interest in canon history and criticism, with special attention to the social reading of canonical books. It then analyses the continuity between canonical and historical readings, before focussing on the issue of diversity in the canon. It concludes by reflecting on this in the light of existing trends towards Biblical Theology and especially Biblical Spirituality as its natural complement.